Comparison of the Gut Microbiota Between Pulsatilla Decoction and Levofloxacin Hydrochloride Therapy on Escherichia coli Infection - Liu, Xiaoye; He, Shangwen; Li, Qiuyue; Mu, Xiang; Hu, Ge; Dong, Hong (Frontiers in Cellular and Infection Microbiology, 2020)
Gut microbiota serves as a critical indicator for gut health during treatment of pathogenic bacterial infection. Both Pulsatilla Decoction (abbreviated to PD, a traditional Chinese medicine compound) and Levofloxacin Hydrochloride (LVX) were known to have therapeutic effects to intestinal infectious disease. However, the changes of gut microbiota after PD or LVX treatment remain unclear. Herein, this work aimed to investigate the changes of intestinal flora after PD or LVX therapy of Escherichia coli infection in rats. Results revealed that PD exhibited a valid therapeutic approach for E. coli infection via the intestinal protection, as well as the inhibited release of IL-8 and ICAM-1. Besides, PD was beneficial to rebuild the gut microbiota via restoring Bacteroidetes spp in the composition of the gut microbiota. Comparatively, LVX treatment promoted the infection and ravaged gut microbiota by significantly decreasing Bacteroidetes and increasing Firmicutes. These findings not only highlight the mechanism of Chinese herbal formula, but extend the application of PD as veterinary medicine, feed additive and pre-mixing agent for improving the production of animal derived foods.